Commande par mode glissant d'un Système éolien basé sur une MADA - سالم, الذهبي; عمار بن محمد, قريرة; محمد العربي, صحراوي (Université d'El Oued, 2021)
"This work presents the study and use of the asynchronous generator GADA for the production of wind energy. To do this, we create a wind turbine model, and a GADA generator model, and we use a sliding mode regulator on the active and reactive power control strategy. This study was concluded with simulation results to validate the models obtained. Keywords: wind power, turbines, dual power asynchronous electricity generator (GADA), modeling, slip control. " يقدم هذا العمل دراسة وإستخدام المولدة اللاتزامنية ذات التغذية المزدوجة "GADA" في إنتاج طاقة الرياح. للقيام بذلك ، نقوم بإنشاء نموذج للعنفة الهوائية ، ثم من المولدة اللاتزامنية "GADA" ،وإعتمدنا على استراتيجية التحكم الإنزلاقي للتحكم في الطاقة الفعالة و الرجعية. وأختتمت هذه الدراسة بنتائج المحاكاة للتحقق من صحة النماذج التي تم الحصول عليها.
Machine éléctrique مذكرة ماستر تخصص
Keywords: wind power, turbines, dual power asynchronous electricity generator (GADA), modeling, slip control; الرياح ، العنفات ، مولدة الطاقة غير المتزامنة مزدوجة التغذية (GADA) ، النمذجة ، التحكم الإنزلاقي